Kunci Sukses Kepemimpinan Di Dunia Digital: Memahami Teknologi Dan Manusia - Amien Barokah, Yusup; Sri Pudjiarti,, Emiliana (Transformasi: Journal of Economics and Business Management, 2024)
. In this discussion, various elements of leadership are discussed, such as education, project management, knowledge management, and physical activity. This study examines how leadership influences student achievement. This emphasizes how important transformative leadership and instructional leadership are to improving student achievement. The results show that project success depends on leadership abilities, confirming the importance of the role of leadership in the project management process. Also discussed is the role of leadership in the effective use of knowledge management. Good leadership is critical to improving organizational performance and helping people share knowledge and manage knowledge. One important factor in the successful implementation of an Enterprise Resource Planning (ERP) system is transformative leadership. Transformative leadership builds an organizational culture that supports and enables people to share knowledge throughout the ERP implementation process. It also studied how people with disabilities view physical activity and how sports professionals can work with them